A Gender Analysis of the Great Recession and “Austericide” in Spain - Gálvez,Lina (2016)
This paper analyses the consequences of the latest recession and austerity measures for the working and living conditions of women and men in Spain, as well as the extent to which gender and other related inequalities are being modified or aggravated. Women are taking on additional responsibilities in terms of unpaid care work due to welfare cuts and privatization, while still facing discrimination in the labour market and in accessing resources and decision-making centres. This refamiliarization of care, together with increasing job insecurity, could have a major negative impact on the well-being of women and their present and future opportunities, which may endanger the fragile gains achieved in terms of gender equality.